La actividad física y su influencia en la calidad de vida de las personas adultas, que sufren enfermedades crónicas no transmisibles del sector puerta negra, cantón Babahoyo, primer semestre 2018 - Sala Medina, Jenifer Katiuska (2018)
Non-communicable chronic diseases occur more frequently in the Ecuadorian population, especially in marginal urban areas, such as: The Puerta Negra sector of the Babahoyo Canton, which is a public health problem. The objective of this project is to evaluate the impact generated by the implementation of a program of physical activities in the quality of life of adults; who suffer chronic non-communicable diseases in the Puerta Negra sector, Babahoyo Canton, first semester 2018. The research is supported by the Public Health Area, under the line Infectious, chronic and degenerative diseases, accompanied by the health promotion model of Nola Pender Theorizer. The study was carried out with 24 people of 30 to 60 years old; who were diagnosed with arterial hypertension, diabetes and obesity. The study methods used are descriptive and analytical, under the quali-quantitative modality, the type of study is applied, longitudinal, prospective, and quasi-experimental, and according to the place it is of field, the techniques used are observation and survey. The Pre-Test Health questionnaire and the Nola Pender lifestyle questionnaire were used for the data collection, as well as the daily observation file. In conclusion, we say that by sending participants to the continuous exercise program and with individual follow-up, weight loss, IMC, abdominal perimeter, and blood pressure are regulated. When performing physical activity in a regular and orderly manner, together with healthy eating, prevents chronic non-communicable diseases.